The Shifting Boundaries of Prejudice Antisemitism and Islamophobia in Contemporary Norway - Christhard Hoffmann (Scandinavian University Press (Universitetsforlaget), 2020)
In recent years, harassment and violent attacks against Jews and Muslims have become issues of concern in many Western countries. However, antisemitism and Islamophobia are often framed as essentially different phenomena, not least as a result of political polarization and deeply divided opinions on both immigration and the Israeli-Palestinian conflict. The present volume challenges this view and argues that antisemitism and Islamophobia are largely related phenomena and linked to xenophobic ideas in the general population. The study is based on varied and comprehensive survey data about attitudes towards Jews and Muslims in Norway, including the attitudes and experiences of the two minority groups themselves. Moreover, it supplements survey analysis with qualitative research, exploring the discursively constructed boundaries of "what can or cannot be said" about Jews and Muslims. Focused on the rich material of the Norwegian case, the volume thus offers new perspectives for the study of prejudice in general.